(untitled) (Revista Argentina de Musicología, 2020)
Today, when contemporary jazz musicians are willing to beyond the canonic tradition of jazz, the music of composer and saxophonist Leandro “Gato” Barbieri acquires a pioneering and groundbreaking significance. With his music, a new musical conversation started between jazz and Latin American folk genres (mainly from Argentina and other regions of South America). Barbieri had been a widely acclaimed musician for a long time in the European free jazz style scene by the time he took a decisive musical turn that would drive his music closer to the cultural and political milieu of his time. His political choices coincided with the onset of civil right movements and a new revolutionary spirit that was rising in Latin America during 1969-1975. As the working title of this paper suggests, I will examine the ways and cultural significance of what could be called the “Third World Music Turn” in the music of Argentina’s most famous jazz musician.